Leaf growth character of sago palm based on sucker weight at the rosette stage. Issue 1 (April 2020) - Nurnawati, A A; Haring, F; Osozawa, K; Dungga, N E
Abstract: The study aimed to obtain suitable sucker recommendation for good growth and development of sago plant in the field and to determine the leaf growth characters based on sucker weight at the rosette stage. The research was conducted at Sago Plantation Site located in Pembuniang Village, West Malangke Sub-district, North Luwu Regency from September to December 2017. The first observation was made at 16-month after sucker transplanting in September 2017, the second in November 2017. To determine statistical differences between the sucker weight of 1-3 kg and 3-6 kg, T-Test (Independent Sample T-Test) was used and Principal Component Analysis (PCA) was used to determine the relationship between the leaf growth characters. The results show the suckers with weight of 3-6 kg grow better than that of 1-3 kg as indicated by the number, width and length of the leaflets, and the number of leaves and rachis length. Sucker with 3-6 kg weight have a closer relationship between variables.